Nurses' decision making authority and position in medical intervention - Füsun Terzioğlu; Fatma Uslu Şahan (Association of Nurse Managers, 2017)
Health care services are one of the most basic, indispensable, non-postponable, and non-negligible needs of community life. Nurses are health professionals who are most likely to be close to the individual during the delivery of health services, during and after the treatment service. For this reason, the nurses may face many situations that may decide on medical interventions related to patient care in health care delivery or may require them to be part of the decisions of this medical interventions. The aim of this article is to examine the nurses' decision-making authority in medical interventions in accordance with laws and regulations, to discuss the position and legal responsibility of the nurse in medical intervention.